(untitled) (Damascus University Journal of Historical Studies, 2023)
Syria has considered one of the most important provinces which Rome has established on the rubbles of ancient monarchies. Its importance stems from the civilizing legacy which this area had had, and the strategic important location on the international trading routs to the far east, furthermore its bordering to a great statehood called Parthia. thus the establishment of the province of Syria had been a significant turning point not just in the Rome’s policy towards the east, but also in the history of the whole region. Hence, this research has aimed to try to understand the reasons that led Rome to change its policy towards the region, and establish the province of Syria, and so the knowledge of the administrative organizations created by pompey on the backdrop of his military campaign to the east.